Apakah blockchain mampu mencegah kecurangan akuntansi? - Rahmawati, Mia Ika; Subardjo, Anang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The increasing number of incidents of accounting fraud in the world has led to demands for changes so that accounting fraud can be reduced or not occur. It takes a technology that is able to provide an advantage in preventing accounting fraud. Blockchain technology, which was originally used as the technology behind bitcoin cryptocurrency transactions, is believed to be able to prevent fraud within the company. The purpose of this study is to analyze how blockchain technology prevents the emergence of accounting fraud. The research method with a qualitative approach is literature study. The result of the research is that smart contracts embedded in the blockchain are able to prevent accounting fraud that occurs in the company. Due to the characteristics of smart contracts and blockchain, users are assured of transparency, trust, immutable and real-time information. So that accounting fraud or fraud can be prevented and significantly improve the quality of accounting products.